Neuroscience study: analysis of mathematical creative thinking ability levels in terms of gender differences in vocational high school students. Issue 1 (June 2021) - Adiastuty, N; Sumarni; Riyadi, M; Nisa, A; Waluya
Abstract: This study aims to determine the mathematical creative thinking abilities Level in the high mathematical creative thinking disposition category for each gender difference. This research is qualitative research using a qualitative descriptive method conducted at SMK Pertiwi Kuningan. This study describes mathematical creative thinking abilities of mathematics learning by collecting descriptive data obtained from the classification dispositions of mathematical creative thinking categories, creative thinking abilities test questions, and valid and reliable interviews. The research subjects chosen were four students from 57 students. The research subjects were two male students and two female students who had creative abilities, and the highest test scores were in the high mathematical creative thinking disposition category. Data analysis was performed with the stages of data collection, reduction, data display, and conclusion drawing. The results showed that male and female students in the high mathematical creative thinking disposition category have creative abilities that fulfill the aspects of flexibility, fluency, and elaboration. Flexibility and fluency aspects have an average score with very good criteria. Then, there are differences in the elaboration aspect, where the average score of female and male students are 3.9 and 3.4, respectively. It shows that the difference is not significant, namely 0.5, which indicates that female students are better at the elaboration aspect. Even so, male students also fulfill the elaboration aspect, wherein the very good criteria both. However, male and female students did not satisfy the originality aspect. The creative ability can be reached by having a high mathematical creative thinking disposition. Therefore, the teacher must be able to instill a high mathematical creative thinking disposition in mathematics learning. The high mathematical creative thinking disposition makes students flexible, fluent, and thorough in solving mathematical problems.